2015
DOI: 10.1159/000438513
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-146a Induced by Hypoxia Promotes Chondrocyte Autophagy through Bcl-2

Abstract: Background/Aims: There have been many studies on the etiology of osteoarthritis (OA) with regard to the function of inflammatory cytokines, the process of cartilage degradation, the function of miR-146a, hypoxia stimulation and autophagy in OA chondrocytes, but there have been no reports on the relationship between miR-146a and autophagy in cartilage, especially under hypoxia. This study aimed to confirm the relationship of miR-146a and autophagy in cartilage under hypoxia. Methods: Chondrocytes were treated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 48 publications
1
47
0
Order By: Relevance
“…In addition, in our study, the IL-1β-induced suppression of miR-92a-3p was reversed with treatment of NF-κB and MAPK inhibitors. A similar negative regulation of ADAMTS-4/5 in chondrocytes by activated NF-κB and MAPKs via miRNAs has been reported previously [42][43][44][45][46], suggesting that miRNAs with similar functions in inflammation and degeneration may be regulated by a common set of catabolic pathways in chondrocytes, including NF-κB and MAPK.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, in our study, the IL-1β-induced suppression of miR-92a-3p was reversed with treatment of NF-κB and MAPK inhibitors. A similar negative regulation of ADAMTS-4/5 in chondrocytes by activated NF-κB and MAPKs via miRNAs has been reported previously [42][43][44][45][46], suggesting that miRNAs with similar functions in inflammation and degeneration may be regulated by a common set of catabolic pathways in chondrocytes, including NF-κB and MAPK.…”
Section: Discussionsupporting
confidence: 81%
“…The expression pattern of miR-146a in cartilage from patients with OA has been identified that miR-146a was intensely expressed in low-grade OA cartilage, suggesting the potential role of miR-146a in OA cartilage pathogenesis [19]. Another investigation indicated that miR-146a could protect cartilage from degeneration in OA, as miR-146a overexpression inhibited hypoxia-induced autophagy in chondrocytes [20]. However the exact role of miR-146a in OA is still unclearly.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-146a, a member of the class of miRNAs, has been found to participate in the pathogenesis of autoimmune diseases such as rheumatoid arthritis (RA), Osteoarthritis (OA), systemic lupus erythematosus (SLE), multiple sclerosis (MS) and GO [3, 9-13]. For instance, MiR-146a was reported to induce TNF-α production by targeting TNF-α/TNF receptor-associated factor 6 (TRAF6)/IL-1 receptor-associated kinase 1 (IRAK1) signaling in RA [14].…”
Section: Introductionmentioning
confidence: 99%